Managing high risk offenders in the community: Compliance, cooperation and consent in a climate of concern. (December 2014) - Weaver, Beth; Barry, Monica
It is increasingly accepted that the change process underpinning the intended outcomes of community supervision, namely community safety, social rehabilitation and reintegration, cannot be achieved without the service user's active involvement and participation in the process. Their consent, compliance and cooperation is therefore necessary to achieving these outcomes and yet, when it comes to very high risk sexual and violent offenders, in the pursuit of community safety, control oriented, preventative practices predominate over change focused, participatory approaches. Semi-structured interviews were conducted with 26 professionals and 26 service users to explore how, under the auspices of MAPPA, the supervisory process is enacted and experienced, and the extent and means through which it affects people's willingness to accept or invest in not only the process but also the purpose of supervision. It is argued that how the process of community supervision is experienced and what it comprises not only shapes the outcomes of supervision but also the nature of consent, compliance and cooperation. We conclude by advocating for more participatory processes and practices to promote service users' active engagement in, and ownership of, the process of change, and in that, the realisation of both the normative dimensions and intended outcomes of community supervision.